2008
DOI: 10.1021/jp8031513
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of the Influence of Base-Step Parameters on the Electronic Coupling between Base-Pair Dimers: Comparison of A-DNA and B-DNA Forms

Abstract: The electronic coupling is one of the key parameters governing electron hole transfer along DNA helices. In this study, we established the first comprehensive data base of electronic coupling elements, calculated at the ab initio level. The data set comprises all possible Watson-Crick base pair dimers, both in standard A-DNA and B-DNA geometries. We also quantified the sensitivity of the coupling elements with respect to geometry changes by varying each of the six standard base step parameters, which specify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 68 publications
5
31
0
Order By: Relevance
“…32 and 51. All of these values are significantly larger than the corresponding V IF estimate at the INDO/S90 level,18 while they are all reasonably similar to the rms-INDO/S in the presence of an adjacent nucleobase 18.…”
Section: Discussion Of Relevant Theoretical/computational Aspectsmentioning
confidence: 61%
See 2 more Smart Citations
“…32 and 51. All of these values are significantly larger than the corresponding V IF estimate at the INDO/S90 level,18 while they are all reasonably similar to the rms-INDO/S in the presence of an adjacent nucleobase 18.…”
Section: Discussion Of Relevant Theoretical/computational Aspectsmentioning
confidence: 61%
“…51 (0.099 eV), our V IF evaluations for the ideal xGC-xGC stack indicate a considerable increase of the transfer integral, hence of the related hole transfer rate, after guanine augmentation (Table 2). This agrees with previous expectations based on the easier oxidability of xG relative to G and the strengthened π–π interactions characterizing xDNA 23,26,55.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Our results are consistent with the studies by Ivanova and co-workers of the structures and electronic couplings between base pairs in A-type versus Btype DNA and LNA:DNA hybrids. 17,20 These workers report somewhat smaller electronic coupling between base pairs possessing stacked purines in A-versus B-type DNA. They also investigated the effect of structural fluctuations on the electronic coupling matrix elements and concluded that they are not perturbed significantly on the nanosecond time scale of base-to-base hole transport by the rigidity of the LNA:DNA duplexes.…”
Section: ■ Concluding Remarksmentioning
confidence: 99%
“…Our results are consistent with the conclusion of Ivanova and co-workers that intrastrand electronic coupling in A-type DNA is slightly smaller than that in B-type DNA. 17,20 ■ RESULTS Synthesis and Spectra of Capped Hairpins. Capped hairpins possessing LNA purine bases L A or L G or pyrimidine bases L T or L C were prepared and characterized by the methods previously described for the A n and A n G m hairpins (see the Supporting Information).…”
mentioning
confidence: 99%